Enhanced mu opioid receptor–dependent opioidergic modulation of striatal cholinergic transmission in DYT1 dystonia. Issue 2 (18th November 2017) - Ponterio, Giulia; Tassone, Annalisa; Sciamanna, Giuseppe; Vanni, Valentina; Meringolo, Maria; Santoro, Massimo; Mercuri, Nicola Biagio; Bonsi, Paola; Pisani, Antonio
ABSTRACT: Background : Mu opioid receptor activation modulates acetylcholine release in the dorsal striatum, an area deeply involved in motor function, habit formation, and reinforcement learning as well as in the pathophysiology of different movement disorders, such as dystonia. Although the role of opioids in drug reward and addiction is well established, their involvement in motor dysfunction remains largely unexplored. Methods : We used a multidisciplinary approach to investigate the responses to mu activation in 2 mouse models of DYT1 dystonia ( Tor1a +/Δgag mice, Tor1a +/‐ torsinA null mice, and their respective wild‐types). We performed electrophysiological recordings to characterize the pharmacological effects of receptor activation in cholinergic interneurons as well as the underlying ionic currents. In addition, an analysis of the receptor expression was performed both at the protein and mRNA level. Results : In mutant mice, selective mu receptor activation caused a stronger G‐protein‐dependent, dose‐dependent inhibition of firing activity in cholinergic interneurons when compared with controls. In Tor1a +/‐ mice, our electrophysiological analysis showed an abnormal involvement of calcium‐activated potassium channels. Moreover, in both models we found increased levels of mu receptor protein. In addition, both total mRNA and the mu opioid receptor splice variant 1S (MOR‐1S) splice variant of the mu receptor gene transcript, specifically enriched in striatum, were selectively upregulated. Conclusion : Mice with the DYT1 dystonia mutation exhibit an enhanced response to mu receptor activation, dependent on selective receptor gene upregulation. Our data suggest a novel role for striatal opioid signaling in motor control, and more important, identify mu opioid receptors as potential targets for pharmacological intervention in dystonia. © 2017 International Parkinson and Movement Disorder Society